UK Government announces interim strategy. Issue 12 (December 2017) - Unknown
Abstract : The UK Government has published its 'Interim Cyber Security Science & Technology Strategy', which lays out how it will go about identifying the technologies that are likely to have the greatest impact on the security of the nation and its businesses and citizens.